STATUS PENANGKAPAN IKAN HIAS DI KEPULAUAN SERIBU TAHUN 2007-2009 (The Status of Ornamental Reef Fish Catch in Seribu Islands (2007-2009)) - Idris Idris; E. Setyawan; A. Mardesyawati (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2011)
Marine ornamental reef fish trade is a huge industry with trade value USD 200-350 million/ year. Seribu Islands, Jakarta is one of the main ornamental reef fish catch area in Indonesia. The aim of this study was to compare ornamental fishing activities with total allowable catch (TAC). Ornamental reef fish catch data were collected from fishermen annually within 2007-2009, while reef fish population data are collected using underwater visual census every two years. The results showed that the total catch of 18 marine ornamental reef fish species exceeded TAC in 2007. Then there were 22 species in 2008 and 17 species of marine ornamental fish in 2009 that their catches were more than TAC. In addition, fish that are always included in the ten highest caught fish within 3 years were Cryptocentrus cinctus, Pomacentrus alleni, Pterosynchiropus splendidus, Premnas biaculeatus, and Amphiprion ocellaris. Their catches exceeded TAC.Key words: Marine ornamental fish, Seribu Islands, Total Allowable Catch (TAC)